EDUKASI PENTINGNYA KEPEMIMPINAN GURU DI ERA SOCIETY 5.0 - Suardi M; Mirfan Mirfan; Guntur Guntur; Muh. Fachrur Razy Mahka; Mila Jumarlis (LPPM Universitas Bina Bangsa, 2023)
The use of innovative information technology in the 4.0 industrial revolution era is expected in society 5.0 as the next era to help human life become more meaningful, especially in the field of education as a quality human factory. The magnitude of the role of the leadership component in preparing teachers as the spearhead of educational success to welcome society 5.0, it is very important to educate teachers to learn to gain understanding regarding teacher leadership in the era of society 5.0, so that they can prepare themselves in building the best future generations who are ready to face his own challenge. The stages of this service start from coordinating time, methods, and material content, then presenting educational material, and evaluating it through a question-and-answer session. The result of this activity is that high school and vocational school teachers know more about the importance of building a spirit of leadership for teachers, especially in welcoming the era of society 5.0 which requires teachers to be able to utilize information technology to make it more meaningful for human life, especially for future students